Answer:
The correct answer is:
Option A. a_n=9+(n-1)(-3)
Explanation:
Given that
a1 = 9
![a_n = a_(n-1)-3](https://img.qammunity.org/2022/formulas/mathematics/high-school/nb8cpuo2qpoffzl4vzmilpx96bzp10bbb0.png)
We can see that in recursive formula the next term is being obtained by subtracting 3 from previous term
That means that the common difference is -3
We also know the first term
The general form of explicit formula for an arithmetic sequence is:
![a_n = a_1 + (n-1)(d)](https://img.qammunity.org/2022/formulas/mathematics/high-school/zbi4v0gvtb8ivpkc5t7zlxpcbqgwjpbtse.png)
We know that a1 = 9 and d = -3
Putting the values we get
![a_n = 9+(n-1)(-3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/7t56xcsbfm9s255vqspnnhv8ojkbmzm67f.png)
Hence the correct answer is:
Option A. a_n=9+(n-1)(-3)